Independent Students In A Learning Environment Teaching To Think - Turakulov X.A.; Kamola Saypillayevna Oslanova (International Scientific and Current Research Conferences, 2020)
This article examines the process of teaching independent thinking to primary school students based on enhanced learning activities. The article can be used by those who deal with the problem of improving the creative abilities of students.